Social impact of ecotourism on livelihood the case of ambulant vendors in Makiling Botanic Gardens, University of the Philippines, Los Baños, Laguna - Rosales, Agnes B.; Maga, Janet P.; Roslin, Ma Anya Yasmin A.; Cerreno, Roberto P.; Tapay, Nenita E. (2010)
The tourism industry provides livelihood to invisible entrepreneurs like the ambulant vendors. This sector is neglected and is defined as illegal by government authorities. Los Baños which is famous for natural springs, food delicacies, handicrafts, and landmarks, particularly the University of the Philippines, is considered a major destination of local and foreign tourists.

Descriptive research was used in this study. Simple random sampling was done in selecting the respondents for the study.

The data show that tourism in Los Baños creates jobs for ambulant vendors of handicrafts and foods particularly, native delicacies. Such livelihood activities affect the social and economic conditions of the vendors. Findings indicate that income from vending is critical for family survival and for improving living standards and the quality of life. The conclusion is that selling activities must be unified and consolidated to sustain and safeguard and vendors' livelihood as well as to strengthen the local ecotourism industry.